Improving KRN.BGT’s Product Knowledge through the List of FAQs on KRN.BGT’s Instagram Stories Highlights - Elrica Puspitasari Yatdiyanto (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Established in April 2020 by Budi Santosa, KRN.BGT is a fashion brand from Jogja Painting that produces artistic masks by collaborating with other local artists. KRN.BGT is targeting people aged 20s-30s who like visual arts. Although it has a well-designed Instagram account, they still receive many questions from their customers and potential customers regarding their products through Instagram direct messages and comments. Therefore, I decided to improve KRN.BGT’s product knowledge by creating a list of FAQs of its products on its Instagram Stories Highlights, compiled from the direct messages and comments by applying the theories of good FAQs by Biroscak (2019) and color contrast from Alscher (2019) and Evans (2019). I found three USPs from my observation and survey, namely adjustable, suitable for adults and children, and customizable; and include them into the list of FAQs, so its existing and potential customers know more about its products. Keywords: product knowledge, FAQ, Instagram, Instagram Stories Highlights